If it's not what You are looking for type in the equation solver your own equation and let us solve it.
a+1/3=2/3
We move all terms to the left:
a+1/3-(2/3)=0
We add all the numbers together, and all the variables
a+1/3-(+2/3)=0
We get rid of parentheses
a+1/3-2/3=0
We multiply all the terms by the denominator
a*3+1-2=0
We add all the numbers together, and all the variables
a*3-1=0
Wy multiply elements
3a-1=0
We move all terms containing a to the left, all other terms to the right
3a=1
a=1/3
a=1/3
| -5y+9.33=-5.84-9.1y | | 6x(3x+8)=16x | | 2+s=3s-8 | | 6x+30=(54) | | 6^x=88 | | –11=z–4+ –7 | | -4(7x+3)=-40 | | C=4w=6 | | {1}{3}(z+4)-6={2}{3}(5-z) | | a+6=-15.2 | | 3/4m=51 | | 10^8a=19 | | -2(4-4x)=40 | | 8x+22=2x+4210x+22=4210x20x=2 | | 2d+10=-30+4d | | -6y+12+9y=8y-3 | | 455-636=646k-(k+8585) | | 12x+311x+9=180 | | 5x+8-7x=-4x+2 | | t/9=18 | | 22.50=r/1.25 | | 3+2x=9x-10 | | 4(5+2x)=84 | | 1/16b=80 | | 5m^2–7m+3=0 | | 5x+4+4x=4 | | –10=w–2+ –9 | | 5(-7x+8)=40 | | 197=19-v | | G=h+1 | | m−9=−27 | | -7(-1x+3)=-14 |